Clinico-biochemical profile of chronic kidney disease patients in elderly age group in a tertiary care centre - Rajkondawar, Atul V.; Yele, Amit (International Journal of Research in Medical Sciences, 2019)
Background: Chronic kidney disease (CKD) remains one of the major health problems in India. Renal function steadily deteriorates as age advances and advancing age has been indicted to have adverse implications in the disease progression to end stage renal disease (ESRD). With the present study, clinico-biochemical profiling of chronic kidney disease patients in geriatric age group as well as comparison with non-elderly patients was undertaken. Methods: In this cross-sectional observational study, 100 patients of CKD admitted in the tertiary care study centre were enrolled consecutively and assessed for symptoms, signs and biochemical parameters over two years. Study subjects were divided into two groups:- Group 1: Elderly patients- aged 60 years or more, and Group 2: Non-elderly patients- less than 60 years of age. Relevant comparisons were drawn statistically and tested for significance. Results: Pallor and pedal edema were observed to be the commonest clinical features across groups. Elderly group shows higher prevalence of severe anaemia (mean hemoglobin- 7.4 gm%). Higher prevalence of clinical and biochemical derangement was found in patients with relatively lower GFR. Elderly age group also had more prevalence of electrolyte abnormalities compared with non-elderly population, with statistically significant difference observed for hyponatremia (p value- 0.023), hypoproteinemia (p value- 0.0078) and blood urea level (p value- 0.0054). Conclusions: Understanding beforehand the biochemical abnormalities associated with old age in CKD patients helps in appropriate modifications in patient management.